Targeted protein degradation by Trim-Away using cell resealing coupled with microscopic image-based quantitative analysis - Kunishige, Rina; Murata, Masayuki; Kano, Fumi (Frontiers in Cell and Developmental Biology, 2022)
“Trim-Away” technology enables rapid degradation of endogenous proteins without prior modification of protein-coding genes or mRNAs through delivery of antibodies that target proteins of interest. Although this approach can be readily applied to almost any cytosolic protein, strategies for cytosolic antibody delivery have been limited to microinjection or electroporation, which require skill-dependent operation or specialized equipment. Thus, the development of antibody delivery methods that are convenient, scalable, and preferably do not require detachment of adherent cells is required to extend the versatility of the Trim-Away method. Here, we developed a cell-resealing method optimized for Trim-Away degradation, which uses the pore-forming toxin streptolysin O (SLO) to permeabilize the cell membrane and delivered the antibodies of interest into HEK293T, HeLa, and HK-2 cell lines. We demonstrated the ability of Trim-Away protein degradation using IKKα and mTOR as targets, and we showed the availability of the developed system in antibody screening for the Trim-Away method. Furthermore, we effectively coupled Trim-Away with cyclic immunofluorescence and microscopic image-based analysis, which enables single-cell multiplexed imaging analysis. Taking advantage of this new analysis strategy, we were able to compensate for low signal-to-noise due to cell-to-cell variation, which occurs in the Trim-Away method because of the heterogenous contents of the introduced antibody, target protein, and TRIM21 in individual cells. Therefore, the reported cell-resealing technique coupled with microscopic image analysis enables Trim-Away users to elucidate target protein function and the effects of target protein degradation on various cellular functions in a more quantitative and precise manner.